Endogen Enzymes: Lipase - Orhan, Cemal Georg; Sahin, Emre; Şahin, Kazım (Turkiye Klinikleri, 2024)
Exogenous enzymes such as phytases, carbohydrases, proteases, and lipases, when added to the diet either individually or in combination, improve the digestibility of crude nutrients by breaking down starch, protein, and lipids. Although lipids are an essential source of energy for poultry, due to low lipase activity, lipid digestion may be inadequate in young animals. Therefore, lipase supplements are important to improve lipid digestibility in animals that reach slaughter weight at an early age, such as broilers. The results of current studies are inconsistent depending on factors such as the lipase source (animal or microbial), dose, and diet content. Lipases produced from microbial sources may be superior to animal lipases in terms of cost and efficacy. Furthermore, studies using different lipase sources in combination with emulsifiers that facilitate the emulsification of fats have shown that lipid digestion and fattening performance can be improved more effectively than when lipases are used alone. In conclusion, due to inconsistencies between studies, research on the use of lipases in poultry should be continued, and optimum dosage and administration methods should be determined.
Keywords: Poultry; enzyme; lipase; digestibility; emulsifiers